2018
DOI: 10.1155/2018/9745639
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy Assessment with a Modified Hybrid Differential Evolution with Model-Based Reinitialization

Abstract: Information literacy assessment is extremely important for the evaluation of the information literacy skills of college students. Intelligent optimization technique is an effective strategy to optimize the weight parameters of the information literacy assessment index system (ILAIS). In this paper, a new version of differential evolution algorithm (DE), named hybrid differential evolution with model-based reinitialization (HDEMR), is proposed to accurately fit the weight parameters of ILAIS. The main contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Yuan Wang (Wang et al, 2018), in his studies, showed that assessing the skills of information literacy students is extremely important. This article explores an improved compression criterion, which is based on the entropy of a population in an objective space and the maximum distance in a decision-making space and is used to make a decision about starting a local search.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yuan Wang (Wang et al, 2018), in his studies, showed that assessing the skills of information literacy students is extremely important. This article explores an improved compression criterion, which is based on the entropy of a population in an objective space and the maximum distance in a decision-making space and is used to make a decision about starting a local search.…”
Section: Literature Reviewmentioning
confidence: 99%